Applying Graph Theory to Some Problems of Economic Dynamics - S. I. Hamidov (Discrete Dynamics in Nature and Society)
This paper studies dynamic models of production and exchange on graph with consideration of transportation costs. Using graph and set of matrices, we introduce superlinear multivalued mappings which describe the exchange ratio in considered system. Effective trajectories of these models are studied. It is shown that trajectories can be constructed using the simplest equilibrium type mechanisms. Characteristics of effective trajectories in Neumann type models are given. Conditions for the existence of equilibrium state of the considered model are found.